1997
DOI: 10.1177/0310057x9702500308
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Cardiovascular Effects of Ketamine Infusion in Patients with Catecholamine-Dependent Heart Failure

Abstract: The longterm effects of ketamine on haemodynamic parameters and exogenous catecholamine requirements were studied in twenty-five critically ill patients with catecholamine-dependent heart failure. Following sedation with midazolam (0.15±0.07 mg.kg-1 .h-1) and sufentanil (0.88±0.33 µg.kg-1 .h-1), patients with impaired left ventricular function (left ventricular ejection fraction area 30±7%) were randomly assigned to receive ketamine (2.5±0.9 mg.kg-1 .h-1) and midazolam (Group A) or remained on sufentanil/midaz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(63 citation statements)
references
References 9 publications
1
62
0
Order By: Relevance
“…Under normal conditions, ketamine stimulates the sympathetic system by increasing circulating catecholamine concentrations (31). Ketamine, however, exhibits potentially negative cardiovascular effects in patients with catecholamine-dependent heart failure (32) or other critical illnesses in which catecholamine is excessively mobilized. Therefore, it may be that the stress of severe burns weakened the sympathetic stimulation and therefore, the cardiac inhibition effect of ketamine became dominant in severe thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, ketamine stimulates the sympathetic system by increasing circulating catecholamine concentrations (31). Ketamine, however, exhibits potentially negative cardiovascular effects in patients with catecholamine-dependent heart failure (32) or other critical illnesses in which catecholamine is excessively mobilized. Therefore, it may be that the stress of severe burns weakened the sympathetic stimulation and therefore, the cardiac inhibition effect of ketamine became dominant in severe thermal injury.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 In contrast, one study reported on a decrease in cardiac index in patients with catecholamine-dependent heart failure when sufentanil was replaced by ketamine. 33 As left ventricular dysfunction and electrocardiographic abnormalities occur frequently after SAH, 34,35 ketamine might be contraindicated in patients presenting with left ventricular failure. In our study patient population, we could not observe clinical relevant cardial abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Reservations for liberal use of ketamine are related to possible development of emergence reactions manifesting as frank delirium, overstimulation of the central sympathomimetic system, and unknown patient tolerance or comprehensive adverse effect profile when administered as a continuous infusion . Current data are limited by small sample sizes, lack of consistent dosing and therapeutic intent, varying definitions and targets of ideal sedation ranges, and inconsistent concomitant pharmacotherapy combinations . Ketamine's appropriate dosing, utility and tolerance as an adjunctive agent, effect on delirium, and adverse effect profile when utilized in the broad critically ill population remains unclear.…”
mentioning
confidence: 99%